BOVINE VIRAL DIARREA VIRUS IN CRIOLLO CATTLE OF THE PROVINCE OF MELGAR, PUNO - Quispe Q., Richard (2008)
The prevalence of bovine viral diarrhea virus (BVDV) infection was evaluated in 347 criollo cattle of both sexes and older than 6 months of age in small herds of the province of Melgar, Puno. Serum samples were tested for antibodies against BVDV using the viral neutralization test. The 48.7 ± 0.1% (166/347) of the samples had antibodies against BVDV. Animals carrying on the virus virus were not detected. Antibodies were detected in all sampled herds and the prevalence varied from 15.7 to 94.1%. Antibodies titers varied from 2 to >256, showing that BVDV infection is widespread in the local cattle population, suggesting the presence of factors promoting the viral distribution such livestock fairs and lack of control for animal movements within the region.